Exploration of salinity and drought stress tolerant endophytic fungi for rice cultivation - Sodhi, Gurleen Kaur (My University, 2024)
The drastic changes in the climate have affected agriculture productivity, and it has become imperative to intensify agricultural production to meet the growing food demand globally. However, the drop in productivity of the crops can be recouped by reducing or adapting to the abiotic stresses they face via exploiting the plant-microbe interaction. Thus, Endophytic fungi play an immense role in bringing out metabolic and physiological changes within the plant to combat or adapt to stress. Hence, this study reports the isolation of fungal endophytes from various plant parts of a rain-fed (PUSA-44) and drought-resistant (Sahbhagi Dhan) rice (Oryza sativa) variety throughout the crop cycle. A total of 182 isolates were obtained from leaves, roots, internodes and spikes of both varieties. Of the total isolates, 120 belonged to the rain-fed and 62 to the drought-resistant rice variety. The highest isolation frequency of 11.6 and 8.8% was observed in roots of rain- fed and drought-resistant varieties, respectively, during the reproductive stage of the plant. The highest diversity of endophytic fungi was also observed at this stage, with a Shannon wiener diversity index (H’) of 2.03 and 1.75 in rain-fed and drought-resistant rice. Among plant parts, the roots of rain-fed rice showed the highest diversity of endophytic fungi with an H’ of 2.13. Whereas in the case of drought-resistant variety, the highest diversity was seen in the internode with H’ of 1.79. Out of the 120 isolates of rain-fed variety, eight isolates (#5OSFS1a, #5OSFL6a, #6OSFL4c, #6OSFI1b, #6OSFR2d, #6OSFR2e, #7OSFS3a and #8OSFI2a) could sustain salinity and drought stress. When it comes to drought-resistant variety, three isolates (#2OSTUL6d, #2OSTUR9a and #4OSTUR1e) isolates demonstrated growth under salinity and drought stress. On evaluating the plant growth-promoting attributes of selected isolates, #6OSFR2e from rain-fed rice and #2OSTUR9a from drought-resistant rice demonstrated the best antioxidant potential against the tested radicals. The isolates exhibited inhibition of gram-ve negative and gram-positive bacteria and antifungal potential. Among the rain-fed isolates, #6OSFR2e had the highest total phenolic content (241.5 ± 4.9 GAE/mg of sample), total flavonoid content (464.4 ± 4.4 QE/mg of sample), indole acetic acid (320.3 ± 5.5 µg/mL), ACC deaminase (317.4 ± 0.4 nmol alpha-ketobutyrate/mg protein/hour) and siderophore production (67.9 ± 0.6%). Whereas among the drought-resistant isolates, #2OSTUR9a displayed the total phenolic content (211.9 ± 0.7 GAE/mg of sample), total flavonoid content (408.4 ± 21.7 QE/mg of sample), indole acetic acid (351.0 ± 7.1 µg/mL), ACC deaminase (305.4 ± 0.8 nmol alpha-ketobutyrate/mg protein/hour) and siderophore production (72.6 ±0.2%). In addition, the isolates also exhibited promising potential in mineral solubilisation, extracellular lytic enzyme and ammonia production. Since isolates #6OSFR2e and #2OSTUR9a were predominantly the top performers, the isolates were identified using morpho-taxonomic and molecular identification tools. The isolates belonged to the same phylum, Ascomycota and were identified as Nigrospora zimmermanii (#6OSFR2e) and Nigrospora oryzae (#2OSTUR9a). Furthermore, the isolates were tested as an inoculum on the rain-fed rice PUSA-44 under a controlled and ambient environment setting. The plants were tested under different stress regimens, including salinity (150 mM NaCl), drought (10% PEG) and combined salinity and drought stress (150 mM NaCl + 10% PEG). Here, compared to the uninoculated plants, the inoculated plants had better physiochemical attributes, relative water content, pigment production, phenolic, flavonoid content, osmolyte accumulation and increased activity of ascorbate peroxidase, catalase, peroxidase and superoxide dismutase. Moreover, a decrease in lipid peroxidation and hydrogen peroxide content was also seen. To the extent of our knowledge, this is the first study demonstrating the plant growth-promoting and abiotic stress mitigation potential of endophytic Nigrospora sp. The findings reported in this investigation open a new realm and can be further explored to potentially replace conventionally used hazardous agrochemicals with a sustainable bioinoculant consisting of endophytic fungi
Keywords: Bioinoculants; pot trials; abiotic stress; climate change; plant growth promotion; fungi